An integrated optimization model for natural gas supply chain. (15th October 2019) - Zarei, Javad; Amin-Naseri, Mohammad Reza
Abstract: Natural gas is a green fossil fuel with the highest demand growth. Natural gas industry is composed of different sectors that form a complex and large supply chain. These sectors make their own decisions individually, resulting in implementation of non-optimal decisions. The aim of this study is to design and optimize an integrated natural gas supply chain (NGSC) formulated as a mixed integer linear programming (MILP) model. The model minimizes total cost and optimizes gas flow between supply chain nodes through pipelines, location-allocation of facilities and pipeline routes along with their capacities, number of pipelines, capacity expansion, extraction, production, storage, exports and imports. The proposed model is applied to a real world case study based on information derived from Iran's NGSC. Finally, the change effect of the most important parameters on the optimal solution is investigated and three actual scenarios are analyzed. The results indicate that the parameters of operating costs and demand volume have a significant effect on the optimal solution and the largest share of supply chain costs is related to operating expenditures. Moreover, the expansion of joint fields and zero import capacity will lead to a remarkable increase in total supply chain costs. Highlights: A novel optimization framework for natural gas supply chain design is proposed. . The integrated strategic and tactical planning of gas supply chain is performed. Location-allocation and capacity expansion of facilities and pipeline routes are considered. Gas storage process in the supply chain is carried out using underground reservoirs.